Smart approach to determine solution of coal quality discrepancy in coal-fired power plant project under binding project finance scheme (case study: PT SBT) - Matiinu Iman Ramadhan; Meditya Wasesa (Universitas Mercu Buana Yogyakarta, 2022)
PT Semangat Berjuang Terus (“PT SBT”) as the developer of the coal-fired power plant with capacity 2 x 950 MW (“the Project”) under project finance scheme was experiencing an issue with the coal suppliers that has been engaged under the Coal Supply Agreement (“CSA”) where coal suppliers could not provide conforming coal in accordance with the specification in CSA. This condition caused the coal suppliers is entering an event of default and it cause PT SBT went into event of default under agreement with financial lenders that potentially affect the eligibility to obtain loan to complete the Project construction. This paper is intended to find the root cause, provide alternative solutions, and finally a recommendation towards the problem that caused by coal quality non-conformity. Using Why-Tree and KT Problem Analysis, the Author identify the root cause of coal quality non-conformity issue is the CSA terms is not applicable to accommodate the practice of coal supply arrangement for power plant project. Based on the Simple Multi Attribute Rating Technique (SMART) analysis method involving key persons from the PT SBT which comes from technical, finance, legal, procurement, and operation side, requesting Lenders waiver to utilize the available coal that acceptable by Contractor, despite the event of default under CSA, is the best option to maintain the eligibility to obtain loan and complete the construction. Furthermore, PT SBT shall amend the CSA in order to mitigate the event of default which occurred because the coal quality will never meet the contract requirement if it remains\